The Role of Emotional Intelligence on Psychological Adjustment and Peer Victimization in a Sample of Spanish Adolescents - Cañas, Elizabeth; Estévez, Jesús F.; Estévez, Estefanía; Aparisi, David (Frontiers in Psychology, 2020)
In the last decades, interest in the study of the negative consequences of bullying for the victims has increased. Victims are often known to show emotional adjustment issues, such as negative self-concept and low life satisfaction. Moreover, some studies have observed important associations between self-concept and life satisfaction, in which a positive self-concept is related to high levels of life satisfaction. Other studies have pointed out the importance of emotional intelligence (EI), as a regulatory and protective factor against the negative impact of victimization on adjustment in adolescents. The main objective of this work was to analyze the mediating effect of self-concept on life satisfaction and the moderated mediation effect of emotional intelligence on self-concept and life satisfaction in the context of peer victimization. The participants in the study were 1,318 Spanish students of both sexes and aged between 11 and 18 (M = 13.8, SD = 1.32) years, from four compulsory secondary education centers. The results indicated that, on the one hand, self-concept mediated the relationship between victimization and life satisfaction. On the other hand, EI was not only positively associated with self-concept, but it also significantly moderated the negative influence of victimization on self-concept. EI may also indirectly moderate the relationship between victimization and life satisfaction through the self-concept. These data show the importance of EI as a possible protective and moderating factor of the negative effect of bullying on emotional adjustment, which is interesting for the design of future prevention and intervention programs in school contexts.